Pengaruh Electronic Word Of Mouth, Saluran Distribusi, Dan Inovasi Produk Terhadap Minat Beli Pada Produk Mie Sedaap : (Studi Pada Mahasiswa Prodi Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Belva Yulivio Estiawan; Andrian; Haryudi Anas; M. Fadhli Nursal; Franciscus Dwikotjo Sri Sumantyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The Influence of Electronic Word of Mouth, Distribution Channels, and Product Innovation on Purchase Interest in Mie Sedaap Products (Study of 2020 Management Study Program Students, Bhayangkara Jakarta Raya University). This research was conducted to investigate the impact of electronic word of mouth, distribution channels, and product innovation on purchasing interest in Mie Sedaap products. This research is research with a quantitative approach. The sampling technique used was simple random sampling, involving 155 respondents who were Mie Sedaap consumers in the Bhayangkara University area, Jakarta Raya. Data processing and hypothesis testing were analyzed using the SPSS version 26 program. The research results showed that there were variables that influenced each other, as explained below: 1) Electronic Word of Mouth partially had a significant positive effect on purchase intention; 2) Distribution channels partially have a significant positive effect on purchasing interest; 3) product innovation partially has a significant positive effect on purchase intention; 4) Electronic word of mouth, distribution channels and product innovation simultaneously influence purchasing interest.